Into the Breach: Using Electronic Resources Responsibly - Geuther, Christina (My University, 2016)
This poster will explain the conversation between technical and public services librarians at Kansas State University regarding data breaches of electronic resources and how to avoid them.  After a recent surge of breaches by Kansas State faculty and students, a workshop was needed for the librarians to relay critical information about resources to the patrons who used them.  This poster will include the protocol at Kansas State University as librarians and Information Technology Security staff are made aware of an issue, simple explanations of breach events, and suggestions for training patrons at the university level to avoid them.  This poster was presented at the 2nd Joint Conference of Kansas Library Association College and University Libraries Section and the Nebraska College and University Section on April 22, 2016.
Citation: Geuther, C. (2016). Into the Breach: Using Electronic Resources Responsibly. Poster was presented at the 2nd Joint Conference of Kansas Library Association College and University Libraries Section and the Nebraska College and University Section, Manhattan, KS.
Keywords: Licensing; Electronic Resources; Breach; Academic Libraries